Erratum: NIELS P. KRISTENSEN, MALCOLM J. SCOBLE & OLE KARSHOLT (2007) Lepidoptera phylogeny and systematics: the state of inventorying moth and butterfly diversity. Zootaxa, 1668, 699747. Zootaxa, 1668, 699-747. - Kristensen, Niels P.; Scoble, Malcolm J.; Karsholt, Ole (Zootaxa, 2008)
(Erratum)